(2,2-Diphenyl-1-picrylhydrazyl) ASSAY of KENIKIR LEAVES (C. caudatus K.), BELUNTAS LEAVES (Pluchea indica L.), AND PURPLE CORN (Zea mays) AS A SOURCE OF ANTIOXIDANTS - Riwanti, Pramudita; Dewi Pinangkaan, Hanifah Mutiara; Mujib, Naili Nabila; Eka Putri, Safira Dinda; Ma’arif, Burhan (Jurnal Farmasi Sains dan Praktis, 2024)
The purpose of this study is to assess and compare the antioxidant activity of the ethanol extract and ethyl acetate fraction of the leaves of Kenikir (C. caudatus K.), Beluntas (Pluchea indica L.), and purple corn seed (Zea mays L.) in an effort to find new sources of antioxidants. The samples were extracted with a 96% ethanol as the solvent. Afterward, the extract was separated using n-hexane and ethyl acetate to get ethyl acetate fraction. The antioxidant concentration was determined using the DPPH free radical technique using spectrophotometer UV-Vis. The results indicate that the purple corn's ethyl acetate fraction has the highest antioxidant activity as a free-radical scavenger, with an IC50 value of 10.47 . The ethyl acetate fraction of P. indica leaves, the P. indica 96% ethanol extract, the C. caudatus leaves 96% ethanol extract, the purple corn's 96% ethanol extract, and the P. indica 96% ethanol extract are all listed after that. The purple corn's 96% ethanol extract has an IC50 value of 21.80 . According to these findings, purple corn has the highest antioxidant activity and may be a new source of antioxidants.